2022
DOI: 10.3390/cancers14225560
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Density Evaluation Improves the Prognostic Values of Staging and p16 in Oropharyngeal Cancer

Abstract: The incidence of oropharyngeal cancers (OPSCCs) has continued to rise over the years, mainly due to human papillomavirus (HPV) infection. Although they were newly reclassified in the last TNM staging system, some groups still relapse and have poor prognoses. Based on their implication in oncogenesis, we investigated the density of cytotoxic and regulatory T cells, macrophages, and Langerhans cells in relation to p16 status, staging and survival of patients. Biopsies from 194 OPSCCs were analyzed for HPV by RT‒… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The protocol was fully described in a previous publication [ 52 ]. To determine the transcriptional status of HPV, all specimens were further immunohistochemically evaluated for p16 expression using a mouse monoclonal antibody (CINtec p16, Ventana, Tucson, AZ, USA) and an automated immunostainer at the Jules Bordet Institute (Bond-Max, Leica Microsystems, Wetzlar, Germany), as described previously [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…The protocol was fully described in a previous publication [ 52 ]. To determine the transcriptional status of HPV, all specimens were further immunohistochemically evaluated for p16 expression using a mouse monoclonal antibody (CINtec p16, Ventana, Tucson, AZ, USA) and an automated immunostainer at the Jules Bordet Institute (Bond-Max, Leica Microsystems, Wetzlar, Germany), as described previously [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study conducted in our laboratory, CD1a-DCs were found to be associated with unfavorable clinical outcomes in patients with advanced laryngeal cancer who had undergone total laryngectomy as the initial treatment [23]. However, only a small number of studies have focused on DC infiltration into laryngeal cancer tissue, but the results differed [24][25][26][27][28][29]; thus, the role of DC infiltration in laryngeal cancer remains unclear.…”
Section: Introductionmentioning
confidence: 98%